Evaluation of Monocarboxylate Transporter 4 in Inflammatory Bowel Disease and Its Potential Use as a Diagnostic Marker. (8th May 2018) - He, Liying; Wang, Hongli; Zhang, Yuhua; Geng, Lanlan; Yang, Min; Xu, Zhaohui; Zou, Kejian; Xu, Wanfu; Gong, Sitang
Abstract : Background. Monocarboxylate transporter 4 (MCT4), encoded by SLC16A3 gene, is responsible for exporting lactic acid into the extracellular microenvironment, and an acidic microenvironment promotes cytokine production and remodels chronic inflammation, providing a link from glycolysis to inflammatory bowel disease (IBD). Objective. The aim of this study is to explore the value of MCT4 as a potential biomarker in IBD. Methods. The study group consisted of 39 cases with UC and 15 cases with CD. The centration of lactate level in serum was assessed by blood gas analysis, and MCT4 expression was analyzed by IHC. Results. Lactate level was increased in the forty-three of 54 patients (79.6%) with IBD by blood gas analysis compared with normal level (P < 0.001 ), in line with the result that showed increased MCT4 expression in inflamed colonic mucosa analyzed by immunohistochemistry. Most importantly, abundance of MCT4 expression was significantly associated with mucosal inflammation, which could be a clinical prognosis marker. Conclusion. The data suggested that increased lactate level in blood was possibly due to highly expressed MCT4 expression caused by inflammation in intestinal mucosal epithelial tissue, which could be a prognosis indicator of IBD in children.